International Organizations and the Media in the Nineteenth and Twentieth Centuries
1 online resource (xiv, 242 pages)
Keywords: "International Organizations and the Media in the Nineteenth and Twentieth Centuries is the first volume to explore the historical relationship between international organizations and the media. Beginning in the early nineteenth century and coming up to the 1990s, the volume shows how people around the globe largely learned about international organizations and their activities through the media and images created by journalists, publicists, and filmmakers in texts, sound bites, and pictures.The book examines how interactions with the media are a formative component of international organizations. At the same time, it questions some of the basic assumptions about how media promoted or enabled international governance. Written by leading scholars in the field from Europe, North America, and Australasia, and including case studies from all regions of the world, it covers a wide range of issues from humanitarianism and environmentalism to Hollywood and debates about international information orders.Bringing together two burgeoning yet largely unconnected strands of researchthe history of international organizations and international media historiesthis book is essential reading for scholars of international history and those interested in the development and impact of media over time."--Provided by publisher.